STUDY ON ORGANIZATIONAL PATHOLOGY AND IMPLICATIONS ON HUMAN RESOURCES JOB SATISFACTION, ALSO ON THE EMPLOYMENT OF THE LABOR MARKET - Diana-Elena, SERB; Nicoleta-Camelia, CICIOC (Strategii Manageriale, 2014)
People need to face the demands resulting induced neurotic styles of their leaders. The result is lower morale, affect behavior, dissatisfaction at work. This paper aims to present the point of view of theoretical and practical implications of failures in the organization on job satisfaction of employees. The practical part of this article is the analysis of statistically labor employment level , and a marketing research field, a survey using questionnaire as the main instrument. The main objectives during the research aims: knowledge labor employment in Romania, identify employee satisfaction on labor relations between managers and subordinates, knowledge of the involvement of the manager in providing a suitable work environment, to determine the extent the problems arising in the workplace creates dissatisfaction which ultimately rebounds on return. The main results drawn as a result of research carried out show that existing pathology in an organization is felt on one side by the employee the aggression and persecution has implications for morale, and on the other hand these disturbances are felt at employment in that workplace, stress employees resign and this leads to higher unemployment.